Sistem Pakar Menentukan Kelas Anak Berkebutuhan Khusus dengan Metode Certainty Factor pada SLB Negeri Serdang Bedagai - Elisa Nur Armaini; Anita Sindar (Journal of Innovation Information Technology and Application (JINITA), 2021)
Parents need to understand the child's condition from an early age, pay attention to the behavior of children who are growing normally in general so that they can take various actions and also other things that are considered important related to the child's future. Choosing to enroll children in special schools is certainly supported by the daily lives of children who do require special behavior in studying school learning. The formulation of the research problem is to determine the class of children with special needs using the Certainty Factor method based on the diagnosis of symptom and characteristic data that can help teachers and parents get information about the types of characteristics of children with special needs students at the State Special School (SLBN) Serdang Bedagai. The characteristics of children with special needs according to the data on the number of symptoms and characteristics discussed are 52 symptoms and 5 characteristics. (Autism JK01, Tuna Grahita JK02, Deafblind JK03, Blind JK04, Tuna Daksa JK05. This application can help teachers and parents find out the characteristics of children with special needs quickly and accurately. This application can be used in every special school to determine early knowing the types of characteristics of children with special needs